Analysis of the Influence of Company Age, Asset Growth and Profitability on the Capital Structure of Sharia Life Insurance Companies Registered at the Financial Services Authority (OJK) for the 2019-2023 Period - Syakirah, Salma; Kristianingsih, Kristianingsih (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Sharia life insurance companies experience capital structure imbalances that can lead to unhealthy financial conditions and increase financial risks. This study aims to determine the effect of Company Age, Asset Growth, and Profitability on Capital Structure based on pecking order theory in Islamic life insurance companies for the 2019–2023 period. The method used is quantitative descriptive with panel data regression analysis techniques. The data used is secondary data obtained from the company's financial statements. The research sample consisted of 21 companies selected by purposive sampling. The results of the study partially show that Asset Growth has no effect, Company Age has a positive effect, and Profitability has a negative effect on Capital Structure. Simultaneously, these three variables have a significant effect on the Capital Structure. This research provides theoretical and managerial implications and adds public insight into the application of pecking order theory in the management of capital structure.